2003
DOI: 10.1021/ef020226i
|View full text |Cite
|
Sign up to set email alerts
|

Asphaltene Aggregation under Vacuum at Different Temperatures by Molecular Dynamics

Abstract: Asphaltene aggregation under vacuum at different temperatures was obtained using classical molecular dynamics (MD) simulations under nonperiodic boundary conditions in a monodisperse system of 96 hypothetical asphaltene molecules. Identical asphaltenes were originally set as an array, where the separation between each other was ∼40 Å. Simulations under the canonical ensemble at NVT conditions, using the Verlet numerical method to solve the motion equations, were conducted. Aggregated systems formed by several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
88
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(100 citation statements)
references
References 25 publications
11
88
1
Order By: Relevance
“…In addition, our result is comparable with those from Molecular Dynamics (MD) simulations that reported an interlayer distance of 3.5-4 Å [73,81].…”
Section: Diagonalsupporting
confidence: 89%
See 2 more Smart Citations
“…In addition, our result is comparable with those from Molecular Dynamics (MD) simulations that reported an interlayer distance of 3.5-4 Å [73,81].…”
Section: Diagonalsupporting
confidence: 89%
“…The energy values reported here seem to be remarkably lower than À55 kcal/mol, the value reported by Pacheco-Sánchez et al [73] for one asphaltene dimer in a vacuum using COMPASS Force Field [74,75], derived using classical Molecular Mechanics (MM) for a parallel arrangement with binding distance of 4 and 5 Å. In another study [76] based on MM and semiempirical calculations, the interaction energy was reported to be À45 kcal/mol for two asphaltene dimers, each containing a hydroxyl group.…”
Section: Diagonalcontrasting
confidence: 69%
See 1 more Smart Citation
“…In recent years there has been an increasing effort to understand asphaltene aggregation on a molecular level using molecular simulation 15,16,17,18,19,20 . The Quantitative Molecular Representation (QMR) method is a vital tool for generating molecular structures for asphaltene simulation.…”
Section: Molecular Dynamics Simulation Of Qmr Generated Asphaltene Stmentioning
confidence: 99%
“…Molecular dynamics (MD) is a good tool to study the molecular structure of bitumen and of the asphaltene nanoaggregates [12][13][14][15]. MD simulations can also quantify the mechanical properties of the material.…”
Section: Introductionmentioning
confidence: 99%